Inhibitory effect of DUP-753 on the drinking responses of rats to central administration of noradrenaline and angiotensin II and to dehydration - Reis, L. C.; Saad, W. A.; Camargo, LAA; Menani, José Vanderlei [UNESP]; Silveira, JEN (Associação Brasileira de Divulgação Científica (ABRADIC), 1996)
We investigated the effect of losartan (DUP-753) on the dipsogenic responses produced by intracerebroventricular (icv) injection of noradrenaline (40 nmol/mu l) and angiotensin II (ANG II) (2 ng/mu l) in male Holtzman rats weighing 250-300 g. The effect of DUP-753 was also studied in animals submitted to water deprivation for 30 h. After control injections of isotonic saline (0.15 M NaCl, 1 mu l) into the lateral ventricle (LV) the water intake was 0.2 +/- 0.01 ml/h. DUP-753 (50 nmol/mu l) when injected alone into the LV of satiated animals had no significant effect on drinking (0.4 +/- 0.02 ml/h) (N = 8). DUP-753 (50 nmol/mu l) injected into the LV prior to noradrenaline reduced the water intake from 2.4 +/- 0.8 to 0.8 +/- 0.2 ml/h (N = 8). The water intake induced by injection of ANG II and water deprivation was also reduced from 9.2 +/- 1.4 and 12.7 +/- 1.4 ml/h to 0.8 +/- 0.2 and 1.7 +/- 0.3 ml/h (N = 6 and N = 8), respectively. These data indicate a correlation between noradrenergic pathways and angiotensinergic receptors and lead us to conclude that noradrenaline-induced water intake may be due to the release of ANG II by the brain. The finding that water intake was reduced by DUP-753 in water-deprived animals suggests that dehydration releases ANG II, and that AT(1) receptors of the brain play an important role in the regulation of water intake induced by deprivation.
Keywords: DUP-753; water intake; angiotensin; noradrenaline